Mad3 and Mad4: novel Max-interacting transcriptional repressors that suppress c-myc dependent transformation and are expressed during neural and epidermal differentiation. - Hurlin, P J (1995)
The basic helix-loop-helix-leucine zipper (bHLHZip) protein Max associates with members of the Myc family, as well as with the related proteins Mad (Mad1) and Mxi1. Whereas both Myc:Max and Mad:Max heterodimers bind related E-box sequences, Myc:Max activates transcription and promotes proliferation while Mad:Max represses transcription and suppresses Myc dependent transformation. Here we report the identification and characterization of two novel Mad1- and Mxi1-related proteins, Mad3 and Mad4. Mad3 and Mad4 interact with both Max and mSin3 and repress transcription from a promoter containing CACGTG binding sites. Using a rat embryo fibroblast transformation assay, we show that both Mad3 and Mad4 inhibit c-Myc dependent cell transformation. An examination of the expression patterns of all mad genes during murine embryogenesis reveals that mad1, mad3 and mad4 are expressed primarily in growth-arrested differentiating cells. mxi1 is also expressed in differentiating cells, but is co-expressed with either c-myc, N-myc, or both in proliferating cells of the developing central nervous system and the epidermis. In the developing central nervous system and epidermis, downregulation of myc genes occurs concomitant with upregulation of mad family genes. These expression patterns, together with the demonstrated ability of Mad family proteins to interfere with the proliferation promoting activities of Myc, suggest that the regulated expression of Myc and Mad family proteins function in a concerted fashion to regulate cell growth in differentiating tissues.